IMPLEMENTATION OF DATA MINING BY USING K-MEANS TO CLASSIFY MARRIAGE AGE - Wiwin Handoko; Auliana Nasution (STMIK Royal, 2023)
Abstract: Marriage is a husband and wife relationship between a man and a woman to form a family. There are several conditions in marriage that must be fulfilled both religiously and legally in force in Indonesia. To carry out the marriage, the prospective bride and groom must register at the nearest Religious Affairs Office (KUA), KUA is an institution established by the government to handle marriage matters. At marriages, various age groups are often found registering at the KUA. This research was conducted using the Data Mining technique through the K-Means Clustering Model to determine the age grouping of marriage which aims to make it easier for the Office of Religious Affairs in educating the prospective bride and groom from a future perspective and an economic perspective in terms of having a child. The research dataset is data on prospective wedding brides at KUA Rawang Lama, Panca Arga in 2022 with a total of 102 samples, by forming 3 clusters, namely: the Ideal cluster of 76 prospective wedding brides (age 19-30 based on husband's age and age 18-25 based on age wife), a good cluster of 20 prospective marriage brides (age 28-44 based on husband's age and age 24-37 based on wife's age), and a risky cluster of 6 prospective marriage brides (age 49-72 based on husband's age and age 39-58 based on wife's age), and produces a Silhouette Score of 0.57. Keywords: clustering; data mining; k-means; marriage Abstrak: Pernikahan merupakan hubungan sebagai suami dan istri antara seorang laki-laki dan perempuan untuk membentuk sebuah keluarga. Terdapat beberapa syarat dalam pernikahan yang wajib dipenuhi baik secara agama maupun secara hukum yang berlaku di Indonesia. Untuk melakukan pernikahan, calon kedua mempelai harus mendaftarkan diri pada Kantor Urusan Agama (KUA) terdekat, KUA merupakan lembaga yang dibentuk oleh pemerintah untuk menangani masalah pernikahan. Pada pernikahan sering ditemukan berbagai kalangan umur yang mendaftarkan diri di KUA. Penelitian ini dilakukan dengan menggunakan teknik Data Mining melalui Model K-Means Clustering untuk menentukan pengelompokkan umur pernikahan yang bertujuan untuk mempermudah pihak KUA dalam mengedukasi calon mempelai pernikahan dalam sudut pandang masa depan dan sudut pandang ekonomi dalam hal memiliki seorang anak. Dataset penelitian ini adalah data calon mempelai pernikahan pada KUA Rawang Lama, Panca Arga pada tahun 2022 sebanyak 102 sampel, dengan membentuk 3 klaster yaitu : cluster Ideal sebanyak 76 calon mempelai pernikahan (usia 19-30 berdasarkan umur suami dan usia 18-25 berdasarkan umur istri), cluster baik sebanyak 20 calon mempelai pernikahan (usia 28-44 berdasarkan umur suami dan usia 24-37 berdasarkan umur istri), dan cluster beresiko sebanyak 6 calon mempelai pernikahan (usia 49-72 berdasarkan umur suami dan usia 39-58 berdasarkan umur istri), dan menghasilkan Silhouette Score 0.57. Kata kunci: clustering; data mining; k-means; pernikahan